Identifying health policy and systems research priorities on multisectoral collaboration for health in low-income and middle-income countries. (10th October 2018) - Glandon, Douglas; Meghani, Ankita; Jessani, Nasreen; Qiu, Mary; Bennett, Sara
Abstract : Introduction: While efforts to achieve Universal Health Coverage (UHC) and the Sustainable Development Goals (SDGs) have reinvigorated interest in multisectoral collaborations (MSCs) among the global health and development community, there remains a plethora of questions about how best to conceptualise, plan, implement, evaluate and sustain MSCs. The objective of this paper is to present research priorities on MSC for health from researchers and policymakers around the globe, with an emphasis on low-income and middle-income countries. Methods: The authors identified 30 priority research questions from two sources: (1) 38 review articles on MSC for health, and (2) interviews and focus groups with a total of 81 policymakers, including government officials (largely from ministries of health and state/provincial departments of health, but also offices of planning, public service, social development, the prime minister and others), large multilateral or bilateral organisations, and non-governmental organisations. In a third phase, questions were refined and ranked by a diverse group of researchers from around the globe using an online voting platform. Results: The top-ranked questions focused predominantly on pragmatic questions, such as how best to structure, implement and sustain MSCs, as well as how to build stakeholder capacity and community partnerships. Despite substantial variation between review articles, policymakers' reflections and online ranking by researchers, two topics emerged as research priorities for all three: (1) leadership, partnership and governance structures for MSCs; and (2) MSC implementation strategies and mechanisms. The review articles underscored the need for more guidance on appropriate study designs and methods for investigating MSCs, which may be a prerequisite for other identified research priorities. Conclusion: These findings could inform efforts within and beyond the health sector to better align research objectives and funding with the evidence needs of policymakers grappling with questions about how best to leverage MSCs to achieve UHC and the SDGs.